EFFECTIVENESS OF ECCENTRIC TRAINING, DYNAMIC RANGE OF MOTION EXERCISES AND STATIC STRETCHING ON FLEXIBILITY OF HAMSTRING MUSCLE AMONG FOOTBALL PLAYERS. (International Journal of Physiotherapy, 2015)
Background: Hamstring stretch is an important part of treatment programs aimed at decreasing the likelihood of hamstring injury. Few studies have examine the effect of eccentric training, static stretching and dynamic range of motion(DROM) exercise in improving hamstring flexibility this study compares the effect of eccentric training and static stretching in improving hamstring flexibility. The purpose of this study was to determine the effects of Eccentric training, Static stretching and Dynamic range of motion (DROM) exercise in improving hamstring flexibility and the second objective is find which technique is more effective in improving hamstring flexibility when compared with a control group. Study design is Experimental pre-test post-test design.Methods: 88 male subjects with limited hamstring flexibility were recruited for this study were assigned to four group. Group1 received eccentric training, group2 received dynamic range of motion exercise, group3 received static stretching and group4 was served as control group. Hamstring length was measured pre intervention and post intervention using a self-monitored active knee extension test.Results: Eccentric training, static stretching and dynamic range of motion exercise showed a significant increase in hamstring length between pre and post intervention. Following a between group analysis done by independent t test revealed a significant difference between group1 group2 and group3Conclusion: It is concluded that eccentric training, dynamic range of motion (DROM) exercise and static stretching groups improved hamstring flexibility.